Principals' Leadership Strategies in Conflict Management in Islamic Boarding Schools - Azzahra, Azzahra; Anugrah, Ruri Liana (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2026)
This study aims to describe and evaluate the principal's leadership strategies in conflict management at the Hayatuddiyar Islamic Boarding School Pekanbaru, as well as to identify the supporting and inhibiting factors. The study employs a descriptive-evaluative qualitative approach, with data collected through in-depth interviews with five informants—consisting of the principal, teachers, educational staff, and female students—complemented by observation and documentation. The results indicate that the leadership strategies implemented include strengthening open communication through a